Minimizing solar insolation in high-rise buildings through self-shaded form - 402209 Chia, Sok Ling (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2008